Metal-induced crystallization : fundamentals and applications - Wang, Zumin (Research scientist); Jeurgens, Lars P. H., 1971-; Mittemeijer, E. J. (Pan Stanford Publishing, 2015)
This book provides the first comprehensive and in-depth overview of the current fundamental understanding of metal-induced crystallization and further elucidates how to employ this process in various technologies, including in thin-film solar cells and display technologies. It aims to give the reader a thorough perspective of metal-induced crystallization and thereby stimulate the development of novel crystalline-semiconductor-based technologies.